TANTANGAN KEBUTUHAN TENAGA KERJA INDUSTRI JASA KONSTRUKSI PROVINSI KALIMANTAN SELATAN - Zain Hernady; Reza Adhi Fajar (Universitas Lambung Mangkurat, 2014)
The provision of construction experts in South Kalimantan can not be separated from the activity of the construction service community, whether from the Owner, the Construction Agents, the Service/skill Supplier, and the Regulator as well as Construction Service User Community. Therefore the improvement for both quantity and quality are not only the responsibility of the Institutions of Skill Service Provider. On the contrary, the supervision of Construction Service Experts implementation in the field must receive appreciation and commitment from the Local Construction Agents, with support of good plans from the the Regulator. Challenges of the fulfillment of worker demands of construction service industry must be viewed from the context of regulation, through the aspects of law, policy, infrastructure, as well as the Construction Management itself. Thus a holistic evaluation study toward the projection of the number of workers and the existence quality in construction service industry in South Kalimantan is obtained. Keyword: construction, regulator, projection.